AGROECOLOGICAL ASSESSMENT OF CHEMICAL ELEMENTS MIGRATION FROM CATCHMENT AREA SOILS OF POSVITSKÉ LAKE (VOLYN POLІSSIA) - Zubkovych, Ivan (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article discusses the ecological status of the catchment areas of Volyn Polіssia lakes, which are formed under the influence of agricultural natural resource management, that leads to organic, chemical pollution and eutrophication of lake reservoirs. From the point of view of the development of the strategy of balanced natural resource management of the lake-basin systems (LBS) of Volyn Polіssia, such searches are relevant. The purpose of the article is to carry out the agro-ecological assessment of migration of biogenic elements, mobile forms of heavy metals and radionuclides in soils of the microcatena of the model catchment area of Posvitské lake for optimization of agricultural natural resource management. The results of the study are based on seasonal semi-stationary studies (2017–2019) by the author and laboratory diagnostics of field materials. The results of the research. Based on the materіals of Earth remote sensing using GIS technologies (ArcMap 10.3 software package), a cartographic model of the spatial and typological structure of the LBS lands of Posvitské lake has been created. The current ecological status has been determined and the economic development of the LBS has been assessed. The results of chemical investigations of the soils of the microcatena of the catchment area have been analyzed. Models of lateral migration of biogenic elements (N, P2O5, K2O,) and cesium-137 radionuclide have been constructed. The agro-ecological assessment of the processes of lateral and radial migration of biogenic elements – easily hydrolyzed nitrogen (N), mobile forms of phosphorus (P2O5), exchangeable potassium (K2O), as well as mobile forms of heavy metals (Cu, Zn, Co, Mn, Pb, Cd) cesium-137 within the soil-geochemical catena of the catchment area has been made. Conclusions. The decrease of the concentration of biogenic elements along the radial profile of the majority of soil sections of the microcatena has been determined. An increase of the content of biogenic elements in the superciliary facies (up to 0.2 m in depth) of the geochemical microcatena and in bottom sediments (0-0.40 m) of the reservoir has been revealed. The catchment area of Posvitské lake is characterized by optimal geo-ecological status and the degree of economic development of the catchment area is very low. The local governments within the lake catchment area need to regulate the intensity of cattle grazing. Measures should be taken to prevent the eutrophication of the lake from the western part of the ater area. Further research should be focused on agro-ecological monitoring of the integrated LBS.